2019
DOI: 10.20491/isarder.2019.655
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Firm Specific Characteristics on The Relation Between Financial Distress And Capital Structure Decisions

Abstract: This study investigates the effect of some of the firm level variables on the relation between financial distress and capital structure decisions. Design/ methodology/approach-The manufacturing firms listed in Turkish market between 2007 and 2017 are analysed. Fixed effect panel regressions are used in the analyses. Findings-Financial distress level increases as leverage and short-term debt maturity usage increase. Firm size, return on equity, asset tangibility variables are reported as effective on the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
(23 reference statements)
3
12
0
Order By: Relevance
“…This evidence also supports the researchsers like Rampini and Viswanath (2020), Joshi (2018) and Lee et al (2011) who pointed towards the moderating role of collaterals. Abdioğlu (2019) confirmed that same results in Turkish firms.…”
Section: Sensitivity Analysis With Feasible Generalized Least Squares...supporting
confidence: 86%
“…This evidence also supports the researchsers like Rampini and Viswanath (2020), Joshi (2018) and Lee et al (2011) who pointed towards the moderating role of collaterals. Abdioğlu (2019) confirmed that same results in Turkish firms.…”
Section: Sensitivity Analysis With Feasible Generalized Least Squares...supporting
confidence: 86%
“…Following Abdioğlu (2019), the third multiple regression model is developed in order to examine the H 4 hypothesis concerned with the moderating effect of firm size on the association between FD and EM:…”
Section: Research Modelsmentioning
confidence: 99%
“…The OPDA funded infrastructure projects for the railways, telegraph, and telephone lines, while also speeding up the commercialisation of the Ottoman economy. 55 Critically, the OPDA gave good credit standing with the creditors of Europe and allowed for additional loans to keep the Empire alive. While this state of financial affairs kept the economy from crashing further, it did put the economic, and in turn, the political situation in a state of dependence.…”
Section: The Crumbling Of the Old Ordermentioning
confidence: 99%